Access to information and participation in communication as basic necessities for the communication structure of Asian countries - Menon, Vijay (2008)
"Access to information". "Participation in communication." These were popular catch phrases during the sixties and the seventies when governments in developing countries made provisions in their national plans calling for widespread public information and popular participation in development planning. Attempts were made to disseminate to the grassroots level information about national development goals, programmes and strategies. Efforts were exerted to enlist citizen involvement and support in the implementation of such programmes. There was great belief that public information and participation would accelerate development and distribute its benefits equitably.